»Werteorientierung« als Grundlage interkultureller Literaturwissenschaft am Beispiel Selim Özdoğans - Schulte Eickholt, Swen (Jahrbuch Türkisch-Deutsche Studien 2020: Wertorientierungen)
Within the context of recent discussions of the performative nature of values, this article argues that literature is especially suited to showing the process of negotiating values. Selim Özdoğan's novel Wo noch Licht brennt portrays the clash of traditional and modern values against a complex intracultural backdrop of late-20th-century Turkey in which the central conflicts are framed by the pressure of a globalized economy on rural communities. The article uses the example of Özdoğan's novel to argue that, in order to take part in the international negotiation of values, literary analyses must investigate how values are portrayed within literary texts.
Keywords: Selim Özdogan; Werte; interkulturelle Germanistik; Gegenwartsliteratur; Transkulturalität; Interkulturalität; deutsch-türkische Literatur

Kommunikationsprobleme. Aspekte der Fingerepisoden in Ulrichs von Liechtenstein "Frauendienst" - Ried, Dennis
Keywords: Ulrich; von Lichtenstein; Frauendienst; Spechtler; Franz Viktor; Erzähler; Minnesänger; Fiktion; Erzählung; Märe; Minnesang; Paso; Germanistik; Wenzel; Horst